PENGARUH MIND MAPPING DAN MOTIVASI INSTRINSIK SISWA TERHADAP HASIL BELAJAR PADA MATA PELAJARAN EKONOMI DI SMA SWASTA TAMANSISWA PEMATANGSIANTAR - Desi Trida Siahaan; Anggun Tiur Ida Sinaga; Tumpal Manahara Siahaan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of mind mapping and students’ intrinsic motivation on learning outcomes in economics subjects at SMA Swasta Tamansiswa Pematangsiantar. The research used a quantitative approach with a quasi-experimental design in the form of a nonequivalent control group design. The population of this study consisted of all tenth and eleventh grade students of SMA Swasta Tamansiswa Pematangsiantar, totaling 362 students. The sample consisted of 133 students selected using cluster sampling techniques. Data collection techniques included observation, pre-test and post-test, questionnaires, and documentation. Data analysis techniques used normality tests, multicollinearity tests, heteroscedasticity tests, multiple linear regression analysis, t-tests, F-tests, and coefficient of determination (R²). The results showed that simultaneously mind mapping and students’ intrinsic motivation had a significant effect on economics learning outcomes. This was proven by the F-test result with a significance value of 0.000 < 0.05. Partially, students’ intrinsic motivation had a positive and significant effect on learning outcomes with a significance value of 0.000 < 0.05. The results also showed a strong and positive relationship between intrinsic motivation and learning outcomes with a correlation coefficient value of 0.78. The coefficient of determination (R²) value of 0.61 indicated that 61% of the variation in learning outcomes could be explained by mind mapping and students’ intrinsic motivation variables, while the remaining percentage was influenced by other factors outside this study. Therefore, it can be concluded that students’ intrinsic motivation plays an important role in improving economics learning outcomes, and the application of mind mapping supported by intrinsic motivation can help improve the quality of learning.